Preformed stainless steel crown in special conditions in adults: Two case reports - S Madhu (Wolters Kluwer Medknow Publications, 2015)
Stainless steel crowns (SSC) are extensively used in child patients. They are mainly used following the pulp therapy in deciduous teeth. They are also used in multi-surface restoration, as an abutment in space maintainers, correction of anterior tooth cross bite, restoration of hypoplasic teeth, etc. In permanent teeth, they are mainly used as interim restorations following root canal treatment in first molars prior to the eruption of permanent second molars. The main advantage of SSC is its limited chair side time, durability and ease of placement. Patients with conditions such as pregnancy and old age who cannot tolerate multiple and long appointments can greatly benefit from the use of SSC. Though SSC can be used by other dental specialties very effectively, its use seems to be limited to pediatric dentistry. Presented here are few adult cases in which SSC is given with good success.